(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2022)
This article explores the role of migrant photo portraiture for life imaging by providing a close reading of two photobooks by contemporary photographer Fazal Sheikh – A Sense of Common Ground (1996) and The Victor Weeps. Afghanistan (1998). Visual storytelling is a core feature of this social and humanitarian photographer’s work, through which two main questions are addressed: how are real-life migration experiences as survival stories and personal biographies inscribed in the portraits of refugees and migrants? Which form(at)s of portraits are chosen, and which practices of portrayal are employed for the purpose of documenting migrant lives? Based on Jean-Luc Nancy’s portrait theory and Giorgio Agamben’s notion of ‘bare life’, the author introduces a process-analytical category of the ‘migrant/refugee portrait’ in order to grasp the complex (de-)figuration processes connected with the sociopolitical issues of human displacement. In Sheikh’s long-term portrayal of migrant/refugee communities and his concept of relational portraiture, she recognizes an effective documentary photo practice for de-othering and demigrantizing the portrait of the migrant as a stereotypical representation of the ‘other’.